Exploration of financial stress indicators in a developing economy. (4th May 2020) - Utkarsh,; Pandey, Asheesh; Ashta, Arvind; Spiegelman, Eli; Sutan, Angela
Abstract: Financial stress scales need to be incorporated into the borrower selection procedure before providing a loan. The three financial stress scales that we examined have strong correlations, but the two involving at least eight questions are better for discriminating between poor and rich. The financial stress indicator that separates male and female students the most is whether financial problems interfere with relationships with other people (interference is more for men). Older students are less satisfied with their financial position and seem to think that their parents worry more about disappointing them for materialistic reasons.